Struktur Vegetasi, Komposisi, dan Serapan Karbon Pekarangan Di Desa Duyung, Kecamatan Trawas, Kabupaten Mojokerto - Nurheni Wijayanto; Agung Prasetyo (Jurnal Silvikultur Tropika, 2021)
Pekarangan is one form of agroforestry that is commonly located in front, back, and/or side of the house. The tiered canopy stratification and varying root depths make agroforestry able to prevent global warming. The purpose of this research is to know the vegetation structure, composition, and carbon absorption of pekarangan in Duyung Village, Trawas Region, Mojokerto Regency. Collecting data using purposive sampling methodwhere the work area is divided into 3 zones, that is theclosest (zone A), the middle (zone B), and the farthest zone (zone C) based on distance from the mountain to the village with 3 samples of pekarangan per zone. The result showed that the highest INP value of stake level is coffee (Coffea sp.) at 45%, the pole level is banana (Musa sp.) at 95%, and the tree level is durian (D. zibethinus) at 55%. Diversity index (H’), wealth index (R), and evenness index (E) at stake level have the highest value. Canopy stratification in all pekarangan is strata C and D. The highest biomass value was found in zone A of 229,95 ton/ha or carbon stock of 105,78ton/ha. Keywords: agroforestry, carbon absorption, species composition, vegetation structure